Genetic Structure and Forensic Feature of 38 X-Chromosome InDels in the Henan Han Chinese Population - Zhang, Lin; Zhu, Zhendong; Du, Weian; Li, Shengbin; Liu, Changhui (Frontiers in Genetics, 2022)
Insertion/deletion (InDel) polymorphisms, as a kind of ideal forensic marker, shows advantages of length variation, low mutation rate and short amplicon size, and have been used in human identification, population genetics and biogeographic research in recent years. X-chromosome genetic markers are important complements in some complex forensic cases. However, the application study of X-chromosome InDel polymorphisms (X-InDels) still need to be explored. In this study, we evaluated the forensic utility of a novel panel including 38 X-InDel markers in a sample of Han population from Henan province in China. We observed that the heterozygosities ranged from 0.0054 to 0.6133, and the combined discrimination power was 1-9.18 × 10–17 for male and 1-7.22× 10–12 for female. The mean exclusion chance in trios and duos were 0.999999319 and 0.999802969, respectively. Multiple biostatistics methods, such as principal component analysis, genetic distances analysis, phylogenetic reconstruction, and structure analysis were used to reveal the genetic relationships among the studied Henan Han group and other 26 reference groups from 1000 Genomes Project. As expected, the Henan Han population was clustered with East Asian populations, and the most intimate genetic relationships existed in three Han Chinese populations from Henan, Beijing and South China, and showed significant differences compared with other continental groups. These results confirmed the suitability of the 38 X-InDel markers both in individual identification and parentage testing in Han Chinese population, and simultaneously showed the potential application in population genetics.